2009
DOI: 10.1073/pnas.0909982107
|View full text |Cite
|
Sign up to set email alerts
|

A structure-based mechanism for benzalacetone synthase from Rheum palmatum

Abstract: Benzalacetone synthase (BAS), a plant-specific type III polyketide synthase (PKS), catalyzes a one-step decarboxylative condensation of malonyl-CoA and 4-coumaroyl-CoA to produce the diketide benzalacetone. We solved the crystal structures of both the wild-type and chalcone-producing I207L/L208F mutant of Rheum palmatum BAS at 1.8 Å resolution. In addition, we solved the crystal structure of the wild-type enzyme, in which a monoketide coumarate intermediate is covalently bound to the catalytic cysteine residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 23 publications
0
64
0
2
Order By: Relevance
“…The catalytic triad of Cys174, His316, and Asn349 is buried deep within each monomer and sits at the intersection of a traditional 16-Å-long CoA binding tunnel and a large internal cavity, in a location and orientation very similar to those of the other plant type III PKSs. A structure-based similarity search using the Dali program (13) suggested that the overall structure of CUS is highly homologous to those of the previously reported plant type III PKSs (rmsds 1.0-1.2 Å and 2.0-2.2 Å for plant and bacterial type III PKSs, respectively), in which the most closely related structural homologue is that of Rheum palmatum benzalacetone synthase (BAS) (PDB entry 3A5Q, Z score ¼ 57.2, rmsd of 1.0 Å over 360 residues aligned with a sequence identity of 53%) (14). R. palmatum BAS produces the diketide benzalacetone by the one-step condensation of 4-coumaroyl-CoA and malonyl-CoA through the formation of 4-coumaroyldiketide acid (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…The catalytic triad of Cys174, His316, and Asn349 is buried deep within each monomer and sits at the intersection of a traditional 16-Å-long CoA binding tunnel and a large internal cavity, in a location and orientation very similar to those of the other plant type III PKSs. A structure-based similarity search using the Dali program (13) suggested that the overall structure of CUS is highly homologous to those of the previously reported plant type III PKSs (rmsds 1.0-1.2 Å and 2.0-2.2 Å for plant and bacterial type III PKSs, respectively), in which the most closely related structural homologue is that of Rheum palmatum benzalacetone synthase (BAS) (PDB entry 3A5Q, Z score ¼ 57.2, rmsd of 1.0 Å over 360 residues aligned with a sequence identity of 53%) (14). R. palmatum BAS produces the diketide benzalacetone by the one-step condensation of 4-coumaroyl-CoA and malonyl-CoA through the formation of 4-coumaroyldiketide acid (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…2 C and D). The coumaroyl binding pocket is also absent in the active-site cavity of R. palmatum BAS, but in this case, the contraction is caused by the simultaneous substitution of the CHS's conserved Thr132 and Phe215 with Leu, along with the conformational change of Ser338, and as a result, the enzyme catalyzes only one condensation with malonyl-CoA to produce the diketide benzalacetone (14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystal structure of BAS also indicated the presence of a putative nucleophilic water molecule that forms hydrogen bond networks with the Cys-His-Asn catalytic triad. Additionally, BAS uses novel catalytic machinery for the thioester bond cleavage of the enzyme-bound diketide intermediate and the final decarboxylation reaction to produce benzalacetone (22).…”
Section: Plant Type III Pkssmentioning
confidence: 99%